The prevalence of depression among patients with tuberculosis: a systematic review and meta-analysis - Bereket Duko; Asres Bedaso; Getinet Ayano (Annals of General Psychiatry, 2020)
Abstract Background Evidence has shown that the prevalence of depression is much higher among patients with tuberculosis (TB) and this, in turn, may adversely impact compliance with anti-TB medications. Therefore, this systematic review and meta-analysis aimed to quantitatively summarize epidemiologic evidence on the prevalence of depression among patients with TB and formulate a recommendation for future clinical practice as well as research. Methods We followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines to conduct this review. We searched PubMed, EMBASE, SCOPUS and Psych INFO to identify relevant studies that investigated the prevalence of depression among TB patients. We also supplemented our electronic search with manual searching to include all pertinent studies in the analysis. We used a Comprehensive Meta-Analysis software version 3.0 (CMA 3.0) to conduct a meta-analysis. We conducted a subgroup and sensitivity analysis and Cochran’s Q- and the I 2-statistics were used to assess heterogeneity. The evidence for the presence of publication bias was checked by using Egger’s test and visual inspection of the symmetry in funnel plots. Results We identified a total of 25 studies that included 4903 participants across seven countries. In our analysis, the pooled estimated prevalence of depression among TB patients was found to be 45.19% (95% CI 38.04–52.55). The prevalence was higher in MDR-TB 52.34% (95% CI 38.09–66.22) than non-MDR-TB 43.47% (95% CI 35.88–51.37) patients. We also found that the pooled prevalence of depression was higher among females 51.54% (95% CI 40.34–62.60) when compared to males 45.25% (95% CI 35.19–55.71). The pooled prevalence of depression was 45.45% as measured by HRDS, and it was 55.62%, 45.52%, and 38.36% as measured by BDI, HADS and PHQ-9, respectively. Conclusion Our finding suggested that the pooled estimated prevalence of depression among tuberculosis patients was relatively high. Screening and management of depression among TB patients were warranted to alleviate suffering. Moreover, the integration of tuberculosis program with regular psychiatry services may substantially reduce the burden.